Development and performance evaluation of a bio-based thermal insulation composite incorporating epoxidized tung oil and waste-derived mineral fillers - Balo, Figen (Springer, 2026)
Increasing environmental concerns, along with the higher needs for greener building materials, have suggested more and more bio-based solutions to replace traditional petroleum-based insulation systems. A new bio-based thermal insulation composite was designed using epoxidized tung oil (ETO) as a renewable binder and waste-derived mineral filler consisting of clay, cement, fly ash, and eggshell powder. The scope was to study the influence of mixture design, ETO amount, and curing temperature on the developed composites' physical, thermal, and mechanical response. The synthesis of the composites led to a maximum number of 36 different composite compositions by adjusting the fly ash-clay ratio, ETO percentage, and curing temperatures. The experimental results include density, thermal conductivity, and compressive and tensile strengths. Both density and thermal conductivity were found to drop significantly with increasing fly ash content, ETO ratio, and curing temperature as a consequence of increasing porosity in the composite matrix. Among all formulations, sample T36 showed the best thermal insulation performance with a density of 1.337 g/cm & sup3; and a thermal conductivity coefficient of 0.253 W/m K, while achieving sufficient compressive strength (7.51 MPa) for nonstructural building envelope applications. Additionally, simulation of building energy using IES-VE demonstrated that the developed composite-based wall systems provided up to 1.5% of energy savings and 1.37% reduction of CO2 emissions in comparison to traditional wall materials. The results suggest that the developed ETO-based composite could be considered a green candidate for thermal insulation application with sustainable mechanical performance and enhanced thermal resistance in addition to waste valorization and environmental burden mitigation.
Keywords: Epoxidized Tung Oil; Bio-Based Insulation Composite; Renewable Materials; Thermal Conductivity; Energy Efficiency; Sustainable Building Materials